Spiritual Intelligence: Vision, Mission, and Character Strengthening Strategies in Education Policy - Hidayat, Mupid; Siswantara, Yusuf; Suryadi, Ace; Ganeswara, Ganjar Muhammad (Universitas Negeri Malang, 2022)
Spiritual intelligence is the soul of national education. Forgetting this creates a gap between ideals and the reality of education. Without mapping, educational understanding can be fragmented so that education is only seen partially. The academic challenge is how to map the education, character, and context of the digital age as well as the threat of disintegration of the nation can be done. Using the method of literature review with descriptive analytics, this research reveals the essence of education as character formation. At the end of the study, the answer was presented with three things: character education is a vision of national education, continuing education as the times becomes the general mission of national education, and adaptive implementation supports the development of the nation's character.